Disrupting Venture Capital. (19th December 2012) - Thurston, Thomas
Abstract Global venture capital is struggling after a decade of poor industry returns. In this environment, relatively recent innovations such as disruptive modeling, OpenIPO, and revenue‐based funding indicate how venture capital may continue to evolve in promising new directions for investors and entrepreneurs alike. © 2013 Wiley Periodicals, Inc.